Low incidence of and mortality from a second malignancy after resection of thymic carcinoma†. (22nd August 2018) - Hamaji, Masatsugu; Kawaguchi, Atsushi; Omasa, Mitsugu; Nakagawa, Tatsuo; Sumitomo, Ryota; Huang, Cheng-Long; Fujinaga, Takuji; Ikeda, Masaki; Shoji, Tsuyoshi; Katakura, Hiromichi; Motoyama, Hideki; Menju, Toshi; et al.
Abstract: OBJECTIVES: Previous studies have suggested that a second malignancy often develops after resection of thymoma; however, it remains unknown whether this is applicable to thymic carcinoma. METHODS: A retrospective chart review was performed based on our multi-institutional database of resected thymic epithelial tumours between 1991 and 2016. A second malignancy was defined as newly diagnosed after thymic tumour resection. The cumulative incidence of and related death from a second malignancy after thymic and neuroendocrine carcinoma resections were estimated using a competing risk model and were compared to those of patients undergoing a thymoma resection. RESULTS: Two hundred and thirty-eight patients were identified (thymic carcinoma 59; thymoma 179). A second malignancy developed in 1 patient (1.7%) with thymic carcinoma and in 17 patients (9.5%) with thymoma. Deaths from second malignancies were noted in 7 patients with thymoma. There was a tendency towards a lower cumulative incidence of and a lower cumulative death from a second malignancy after thymic carcinoma resection ( P  = 0.139 and P  = 0.20, respectively) than after thymoma resection. The cumulative incidence of a second malignancy in patients with thymic carcinoma was 2.8% at 5 years and at 10 years (8.0% at 5 years and 11.8% at 10 years in patients with thymoma). CONCLUSIONS: After resection of thymic and thymic neuroendocrine carcinoma, the probability of developing a second malignancy, as well as mortality from a second malignancy, is very low. A prospective study with a larger sample size is required to validate our results.